NECROTIC SOFT TISSUE INFECTION DEVELOPED AFTER INSECT BITES: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Bababekov, A.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Results: Among the treated patients in the control group, there was one lethal outcome, and two patients underwent amputation of the affected limb due to the progression of the process. In the main group, one patient underwent amputation of the upper limb due to progressive necrosis; the other patients managed to save the limb. The analysis of complications and lethality allowed us to identify the main reasons for the process progression, which include conservative therapy with waiting tactics (waiting for clinical signs of purulent process development), inadequate primary surgical interventions (small incisions), incomplete necrosectomy ('sparing' tactics), inadequate antibacterial therapy (small doses, lack of previous antibiotic therapy). When such tactics are carried out, the inflammatory process does not stop and becomes necrotic. Toxic necrosis rapidly spreads to neighbouring other tissues, expanding the zone. At the same time, there is no active purulent discharge. Conclusion. Thus, to improve the treatment results of patients after insect bites and to prevent the progression of necrotic changes in soft tissues, early surgical intervention with adequate antibacterial therapy and differentiated local management of the wound process is necessary.